1996
DOI: 10.1046/j.1365-2141.1996.d01-1681.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of busulphan versus total body irradiation combined with cyclophosphamide as conditioning for autograft or allograft bone marrow transplantation in patients with acute leukaemia

Abstract: We retrospectively compared the outcome in patients in the EBMT database transplanted for acute leukaemia from January 1987 to January 1994 who received busulphan and cyclophosphamide (BU/CY) as a pretransplant regimen versus those who received cyclophosphamide and total-body irradiation (CY/TBI). The patients were matched for type of transplant (autologous bone marrow transplantation (ABMT) versus allogeneic (BMT)), diagnosis (acute lymphoblastic leukaemia (ALL) or acute myeloid leukaemia (AML)), status (earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 13 publications
6
97
1
2
Order By: Relevance
“…An early report found no difference in outcome between TBI-and BUbased regimens in ALL in CR1, but demonstrated better 2-year leukemia-free survival for TBI-based regimens (34 vs 14%; P ¼ 0.002) in patients with advanced disease. 2 A retrospective study of 156 patients with ALL treated with autologous or allogeneic HCT found an increased risk for relapse (71 vs 47%; P ¼ 0.01) and lower 6-year PFS (22 vs 43%; P ¼ 0.01) in patients treated with BU. 3 Another retrospective study of 221 patients with ALL treated with AHCT also found improved disease-free survival for patients treated with TBI compared with BU (26 vs 17%; P ¼ 0.04).…”
Section: Introductionmentioning
confidence: 99%
“…An early report found no difference in outcome between TBI-and BUbased regimens in ALL in CR1, but demonstrated better 2-year leukemia-free survival for TBI-based regimens (34 vs 14%; P ¼ 0.002) in patients with advanced disease. 2 A retrospective study of 156 patients with ALL treated with autologous or allogeneic HCT found an increased risk for relapse (71 vs 47%; P ¼ 0.01) and lower 6-year PFS (22 vs 43%; P ¼ 0.01) in patients treated with BU. 3 Another retrospective study of 221 patients with ALL treated with AHCT also found improved disease-free survival for patients treated with TBI compared with BU (26 vs 17%; P ¼ 0.04).…”
Section: Introductionmentioning
confidence: 99%
“…The use of TBI as a part of conditioning regimens for this type of treatment continues in the modern era, and appears to provide benefit over conditioning with chemotherapy alone in many settings [17][18][19][20] (Table 1). Although huge amounts of progress have been made with regard to optimal BMT methods in the past 50 years, myriad questions regarding technique and outcome remain.…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%
“…Bu/CP-based regimens have been reported in most studies to be as effective as a TBI-containing regimen for allograft recipients with acute leukemia and chronic myeloid leukemia (CML). [3][4][5][6] However, a randomized French study showed that TBI was better than Bu in patients undergoing BMT for AML. 7 A higher transplantation-related mortality occurred in patients with advanced disease on a Bu-containing regimen, compared to TBI in another randomized trial.…”
mentioning
confidence: 99%